Co-operation of electricity and natural gas systems including electric vehicles and variable renewable energy sources based on a continuous-time model approach - Nikoobakhta, Ahmad; Aghaei, Jamshi; Shafie-khah, Miadreza; Catalão, João P.S. (Elsevier, 2020)
This paper proposes a stochastic framework to augment the integration of variable renewable energy sources (VRESs) in power system scheduling. In this way, the fast-response capability of gas-fired generator units (GFGUs) and vehicle-to-grid (V2G) capability of electric vehicles (EVs) can play important roles in large-scale integration of VRESs. However, the growth of GFGUs utilization can increase the grade of interdependency between power and natural gas systems. In this condition, the power system tends to demand more reliability and flexibility from the natural gas system, which creates new challenges in power system scheduling. The likely significant growth of EVs can solve this challenge and reduce the correlation between power and natural gas systems, bringing new opportunities for power system scheduling. However, a considerable literature in the field of operation of GFGUs and EVs has only focused on using the hourly discrete time model (HDTM). Undoubtedly, the major limitation of HDTM is its inability to handle the fast sub-hourly dispatch of GFGUs and energy storage capability of EVs. Accordingly, in this paper, this limitation has been solved by the operation of both energy systems with a continuous time model (CTM). The reliability test system with a ten-node gas transmission system has been analysed to show the effectiveness of the proposed problem.
Keywords: natural gas; production of electricity; renewable energy sources; electric vehicles; energy production (process industry); energy; sources of energy; energy market; energy systems; gases; fi=Sähkötekniikka|en=Electrical Engineering|